If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 7x + -5 = 0 Reorder the terms: -5 + x + 7x = 0 Combine like terms: x + 7x = 8x -5 + 8x = 0 Solving -5 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 8x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 8x = 0 + 5 8x = 0 + 5 Combine like terms: 0 + 5 = 5 8x = 5 Divide each side by '8'. x = 0.625 Simplifying x = 0.625
| 56=6h | | 6y-25=95+y | | 24=c-8 | | 4x+7=23+2x | | 40+3x+20+x=180 | | https://homebase.schoolnet.com/files/assess_files/cf1ae17e-8d5e-4dca-981c-c9ee7af1d787/_s_I373865_1.png | | 6-7a-14=8+a | | 4x+81=13x+36 | | 9+2j=17 | | 7x+5-3y=-31 | | 12x-19y+27=1 | | 6(x-5)-3w=12 | | 3x+3*5=27 | | 10=4+3s | | 4x^3-15x^2-25x= | | -114=-2x+3(4x+2) | | 9+-1y+2y=14 | | w+19=40 | | -5c+2=4x+29 | | 7x+3x+9=5x+34 | | 7(5-z)=56 | | 10x-.66(9x+6)=4x-23 | | 3(x+50)-10=2(x+20) | | -7(2x+5)=2(-7x+10) | | -7(6-x)=24 | | 9(-1-x)=72 | | 7(2x-5)=43 | | (-35y-45y)/5y= | | 1/6y-6=-15 | | 4y-2=66 | | (-35y-45y)/5y | | 51/12 |